2017
DOI: 10.3389/fnhum.2017.00214
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Ankle Foot Orthosis Deteriorates Mediolateral Balance Control and Vertical Braking during Gait Initiation

Abstract: Rigid ankle-foot orthoses (AFO) are commonly used for impeding foot drop during the swing phase of gait. They also reduce pain and improve gait kinematics in patients with weakness or loss of integrity of ankle-foot complex structures due to various pathological conditions. However, this comes at the price of constraining ankle joint mobility, which might affect propulsive force generation and balance control. The present study examined the effects of wearing an AFO on biomechanical variables and electromyogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…may also be expected to modify stance leg stiffness. On this aspect, Delafontaine et al[ 51 ] showed that wearing an orthosis over the ankle of the stance leg induced an increase in the mediolateral fall of the center of mass. In contrast, unpublished observations from our laboratory showed that wearing an orthosis over the knee of the stance leg did not induced any change in the mediolateral fall of the center of mass.…”
Section: Stabilizing Mechanisms Into Play During Gait Initiationmentioning
confidence: 99%
“…may also be expected to modify stance leg stiffness. On this aspect, Delafontaine et al[ 51 ] showed that wearing an orthosis over the ankle of the stance leg induced an increase in the mediolateral fall of the center of mass. In contrast, unpublished observations from our laboratory showed that wearing an orthosis over the knee of the stance leg did not induced any change in the mediolateral fall of the center of mass.…”
Section: Stabilizing Mechanisms Into Play During Gait Initiationmentioning
confidence: 99%
“…Gait initiation is a functional task that is classically used in the literature as an experimental paradigm to investigate how the central nervous system (CNS) controls balance in dynamical conditions in both healthy adults [e.g., (31)(32)(33)(34)(35) for recent articles] and pathological patients [e.g., (36)(37)(38)(39)(40) for recent articles]. Gait initiation appears to be the major biomechanical model, complementary to the classical clinical test, in order to predict postural disorders in elderly fallers and non-fallers (41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of dorsal flexion during the swing phase led to an inappropriate IC in the next stance phase, thereby giving rise to the risk of stumbling. Although dorsal flexion was successfully assisted, however, the forward ability during the stance phase decreased significantly [22]. Then, researchers improved on the AFO by giving it a controllable ankle joint, thereby giving rise to the flexible rigid AFO and articulated AFO.…”
Section: Types Of Afo Structuresmentioning
confidence: 99%